2001
DOI: 10.5194/hess-5-225-2001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parameter estimation uncertainty in Kriging: Part 2 - Test and case study applications

Abstract: The theoretical approach introduced in Part 1 is applied to a numerical example and to the case of yearly average precipitation estimation over the Veneto Region in Italy. The proposed methodology was used to assess the effects of parameter estimation uncertainty on Kriging estimates and on their estimated error variance. The Maximum Likelihood (ML) estimator proposed in Part 1, was applied to the zero mean deviations from yearly average precipitation over the Veneto Region in Italy, obtained after the elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 6 publications
0
10
0
5
Order By: Relevance
“…The entity and the importance of the bias and of the increase in variance will be elaborated in Part 2 by means of a case study based upon the average yearly precipitation over the Veneto Region in Italy (Todini et al, 2001). Although, for the sake of simplicity, the development of the methodology in this paper does not consider errors in data, it can be expanded easily to take them into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The entity and the importance of the bias and of the increase in variance will be elaborated in Part 2 by means of a case study based upon the average yearly precipitation over the Veneto Region in Italy (Todini et al, 2001). Although, for the sake of simplicity, the development of the methodology in this paper does not consider errors in data, it can be expanded easily to take them into account.…”
Section: Discussionmentioning
confidence: 99%
“…The application of the technique to real data with this independence hypotheses showed that the assumption of independent errors may involve significant distortions in the estimation of the parameters particularly for certain types of variograms (Todini et al, 2001).…”
Section: The Maximum Liklihood Estimatormentioning
confidence: 99%
“…Obviously, this introduces additional uncertainties related to the many processes involved in the rainfall-runoff transformation and the modelling scheme used, and makes the validation of downscaling models only affordable in an indirect and therefore scarcely reliable way. To overcome this difficulty, standard synthetic tests based on Monte Carlo approaches should be set up and, most important, agreed upon by the hydrological and meteorological communities, to test objectively the different approaches in terms of expectation and reduction in uncertainty (Todini, 2001). Nonetheless, the investigation of detailed case studies is of great relevance and must be encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to full Bayesian approaches, in view of these difficulties, a new technique is presented by Todini (2001) and demonstrated for the interpolation of the rainfall field in a region (Todini et al, 2001).…”
Section: Stochastic Interpolation Techniquesmentioning
confidence: 99%
See 1 more Smart Citation